The Bombay boomerang - Dixon, Franklin W. (New York Grosset & Dunlap, 1970)
The Hardy boys dial a wrong number, get the Pentagon, and suddenly find themselves in a dangerous adventure involving national security.
Keywords: Mystery and detective stories